2009
DOI: 10.1111/j.1540-6520.2009.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Business, Identity Conflict, and an Expedited Entrepreneurial Process: A Process of Resolving Identity Conflict

Abstract: Drawing on Identity Control Theory (ICT) and the literature on social identity, we offer a model of the dynamics associated with competing family and business identities brought into conflict by "family-business" events. We introduce the notion of the family-business role as a distinct identity functioning at the intersection of family and business identities. This meta-level identity "manages" conflict between the family and the business identities, and is formulated and transformed within the family structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
199
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(225 citation statements)
references
References 84 publications
(130 reference statements)
2
199
0
10
Order By: Relevance
“…These synergies could positively contribute to the performance of the family firm (Kellermanns and Eddleston 2004) and to the entrepreneur's and family members' psychological well-being (Shepherd and Haynie 2009b). Research has suggested, for instance, that systemic family influences can enhance firm success (Habbershon et al 2003;Kellermanns and Eddleston 2004).…”
Section: Identity Identity Conflict and The Entrepreneurial Firmmentioning
confidence: 99%
See 3 more Smart Citations
“…These synergies could positively contribute to the performance of the family firm (Kellermanns and Eddleston 2004) and to the entrepreneur's and family members' psychological well-being (Shepherd and Haynie 2009b). Research has suggested, for instance, that systemic family influences can enhance firm success (Habbershon et al 2003;Kellermanns and Eddleston 2004).…”
Section: Identity Identity Conflict and The Entrepreneurial Firmmentioning
confidence: 99%
“…In a similar way, we define the business owner identity as the set of behavioral expectations associated with the business owner role (Shepherd and Haynie 2009b). Both psychological and business perspectives generally state that the role as a business owner is associated with expectations about behaviors that yield extrinsic returns (e.g., growth, financial earnings, public recognition) (Kuratko et al 1997), commitment to the firm and its members (Muse et al 2005), legitimacy in a social context (Malach-Pines et al 2005), and security and prosperity for the family (Kuratko et al 1997).…”
Section: Identity Identity Conflict and The Entrepreneurial Firmmentioning
confidence: 99%
See 2 more Smart Citations
“…While research has explored work-life balance among entrepreneurs (Shepherd & Haynie, 2009a, 2009b, we know little about how entrepreneurs continue to achieve work-life balance when the work aspect of this relationship has ended in failure. For instance, is an entrepreneur able to compartmentalize a failure into his or her work micro-identity, thus making the failure have minimal effect on other micro-identities (e.g., the "spouse" microidentity), or does the failure lead to spillover effects?…”
Section: The Social Implications Of Entrepreneurial Failurementioning
confidence: 99%